2003
DOI: 10.21608/ejabf.2003.1785
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Pollution in Surface Muddy Sediments of Lake Urullus,southeastern Mediterranean, Egypt

Abstract: T he concentrations of certain heavy metals (Cd, Co, Cr, Cu, Fe, Mn, Ni, Pd and Zn) in the total and labile fractions of muddy sediment samples collected from eleven sites in Lake Burullus in January 2003 were investigated in order to evaluate the pollution status of the Lake. The metal contents were determined by means of Atomic Absorption Spectrophotometer (AAS) using MESS-2 certified reference material (National Research Council of Canada). The average concentrations of the heavy metals analyzed in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
6
15
0
Order By: Relevance
“…Similar work was done by El Nemer [36] on sediments from Lake Burullus (MPI = 162.5) and comparing with those done it was found that in the current work the MPI is less than calculated by [36]. The MPI was calculated for the studied elements from different work and MPI for Upper Continental Crust UCC content of the 6 elements as shown in Table 7.…”
Section: Assessment Of Contamination Parameters From Heavy Metals Metsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar work was done by El Nemer [36] on sediments from Lake Burullus (MPI = 162.5) and comparing with those done it was found that in the current work the MPI is less than calculated by [36]. The MPI was calculated for the studied elements from different work and MPI for Upper Continental Crust UCC content of the 6 elements as shown in Table 7.…”
Section: Assessment Of Contamination Parameters From Heavy Metals Metsupporting
confidence: 70%
“…It could be explained by existence of the studied area in the west of Nile Delta near to Sadat City. MPI has a significance value from the work done in [36] which is higher three times than the MPI in the present work because of Lake of Burullus is a closed aquatic system and the disposal rate of waste from industry and sewage is high. …”
Section: Assessment Of Contamination Parameters From Heavy Metals Metmentioning
confidence: 59%
See 1 more Smart Citation
“…An aliquot of 0.5 g of dry sediment (mud or sand) was shaken with 1N HCl (40 ml) at room temperature for two hours (El Nemr, 2003;Villares et al, 2003). The suspension was filtered on the nuclepore 0.4 μm polycarbonate filters, previously treated with 6M HCl and Ultra-pure water, then with 1M CH 3 COONH 4 and finally with 100 ml ultra-pure water (triplicate extractions were made for each sample).…”
Section: Determination Of Leachable Heavy Metalsmentioning
confidence: 99%
“…Analysis of the leachable (labile) metal fraction of the sediment may be more useful, in terms of discovering its biological significance and the new inputs, than analysis of the total metal fraction (Lacerda et al, 1992;Puente et al, 1996;El Nemr, 2003). However, sediment analysis is more indicative than water analysis for evaluating the degree of contamination in the aquatic medium.…”
Section: Introductionmentioning
confidence: 99%